Volatile organic compounds of Thai honeys produced from several floral sources by different honey bee species - Praetinee Pattamayutanon (2018)
©2017 Pattamayutanon et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. The volatile organic compounds (VOCs) of four monofloral and one multifloral of Thai honeys produced by Apis cerana, Apis dorsata and Apis mellifera were analyzed by headspace solid-phase microextraction (HS-SPME) followed by gas chromatography and mass spectrometry (GC-MS). The floral sources were longan, sunflower, coffee, wild flowers (wild) and lychee. Honey originating from longan had more VOCs than all other floral sources. Sunflower honey had the least numbers of VOCs. cis-Linalool oxide, trans-linalool oxide, ho-Trienol, and furan-2,5-dicarbaldehyde were present in all the honeys studied, independent of their floral origin. Interestingly, 2-phenylacetaldehyde was detected in all honey sample except longan honey produced by A. cerana. Thirty-Two VOCs were identified as possible floral markers. After validating differences in honey volatiles from different floral sources and honeybee species, the results suggest that differences in quality and quantity of honey volatiles are influenced by both floral source and honeybee species. The group of honey volatiles detected from A. cerana was completely different from those of A. mellifera and A. dorsata. VOCs could therefore be applied as chemical markers of honeys and may reflect preferences of shared floral sources amongst different honeybee species.